Knowledge Mapping of Immunotherapy for Hepatocellular Carcinoma: A Bibliometric Study - Shen, Jianming; Shen, Hui; Ke, Lixin; Chen, Jialin; Dang, Xi; Liu, Baoxian; Hua, Yunpeng (Frontiers in Immunology, 2022)
Abstract Background: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors, which has progressed to an advanced stage at the time of discovery. In recent years, with the clinical application of immunotherapy drugs, the treatment of advanced liver cancer has made phased progress. A lot of articles about immunotherapy for HCC have been published, but no relevant bibliometric study has been published. This study aims to understand the current situation and explore the new research direction through the analysis of the literature related to immunotherapy for HCC. Methods: We searched articles related to immunotherapy for HCC in the Web of Science Core Collection (WoSCC). Three softwares (VOSviewer, CiteSpace and python) were mainly used to analyze the contribution and cooccurrence relationships of various countries/regions, institutes, and authors and to reveal research hotspots and promising future trends in this research field. Results: A total of 1641 English articles published between 2011 and 2020 were obtained and the number of articles increased almost every year. Most publications came from China (n=893, 54.42%), followed by the United States and Japan. The Sun Yat-sen University contributed the most publications (n=97, 5.91%). Nakatsura Tetsuya (n=26) and Llovet JM (n=366) ranked first both in the top-ten authors and co-cited authors. The Cancer Immunology Immunotherapy is the most productive academic journal on immunotherapy for HCC [n=46,2.80%; impact factor (IF)=6.9679]. Aggregation and key nodes in the co-cited network revealed the change of topics in HCC immunotherapy field. In the early studies, the hotspots mainly included “glypican-3”, “cytokine-induced killer cells” and “ny-eso-1”. While in recent years, the focus has transformed to “landscape”, “camrelizumab”, “combination therapy” and “immune score”. Conclusion: With the breakthrough progress of immunotherapy in HCC, increasing attention has been paid. Nowadays, the hot frontiers are mainly present in understanding immune landscape of liver cancer, screening the population that can benefit from immunotherapy and the clinical application of immune checkpoint inhibitors, especially combination between immune checkpoint inhibitors and other treatment options (such as local therapy, targeted therapy and so on).